Comparative study of various knowledge management systems in higher Education. - et. al., Dr. Ajim Shaikh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Managing knowledge has become very important in this century because this is an era of information overload, i.e. everyone is bombarded with so much of information that a separate system needs to be developed to manage the knowledge. Every organisation has a lot of knowledge with the people working in the organisation but often it happens that the organisation lacks specific knowledge needed at any particular point of time. This happens not because the organisation lacks the knowledge needed but because the knowledge is not managed well to make it available to the right person at the right time. Because of these prevailing situations in organisations, there is a requirement of gathering, alteration, distribution and utilisation of knowledge. This process of gathering, altering, distribution and utilisation of knowledge is labelled as Knowledge Management. The paper addresses the different knowledge management practices used in the higher education sector.